Proposal of a hybrid decision-making model for the alignment of the environmental performance - Boulagouas, Wafa; Chaib, Rachid; Djebabra, Mébarek (Management of Environmental Quality, 2020)
Purpose Decoupling of pressures ranging from regulatory compliance and stakeholders expectations to business competitiveness and sustainability, companies need to align their environmental strategies with a broader consideration of these influences. This paper aims at developing a dynamic alignment model to enhance the environmental performance that considers the influential pressures based on a multi-criteria decision-making process. Design/methodology/approach Authors have proposed a dynamic model for the alignment of the environmental performance based on a hybrid multi-criteria decision-making approach combining the analytic hierarchy process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This model considers contemporary strategic dynamism of the environmental performance and provides a methodology to assist companies prioritizing the environmental aspects based on the influential pressures and deciding on the enhancement pathways. Findings The proposed model based on a hybrid multi-criteria decision-making process allows prioritizing the environmental aspects considering the allocated weights to the alignment-triggered pressures and draw the way to develop different pathways to improve the alignment. Practical implications The proposed dynamic alignment model presents an instrument for the continuous alignment of the environmental performance and an effective management of changes and contributes to minimize gaps and divergences. Originality/value In this paper, the environmental performance has been approached through the contemporary strategic dynamism with the deployment of the multi-criteria decision-making techniques to yield an alignment framework for the environmental decision that combines the internal and external approaches for an effective and sustainable improvement of the environmental performance.